Opportunities and prospects of the phytotherapy of different forms of mastopathy - O. V. Tikhonovskiy (Zaporozhye State Medical University, 2015)
Taking into consideration the frequency of breast pathology and limited possibilities of pharmacological treatment, question of medicinal plants connectivity to complex therapy is very relevant. In order to identify prospects of herbal treatment of mastopathy, the article analyzes key aspects of pathogenesis of mastopathy various forms, which may be affected by phytopreparations. The literature on this issue gives pharmacological properties of different groups of gonadotropin plants based on their impact on different pathogenetic changes in women, that occur in this disease and generalize comprehensive approach on the formation of lines and principles of phytotherapy in this condition using groups of plants with different pharmacological properties. It is determined, that in some situations, herbalism not possible or permissible, but generally it is strictly necessary and, in fact, it is the only effective therapeutic method, also relatively safe with proper selection of combinations and under doctor's control, who is a specialist in phytotherapy. This testifies prospects of herbal medicine in mastopathy.